Preclinical and Clinical Epigenetic-Based Reconsideration of Beckwith-Wiedemann Syndrome - Papulino, Chiara; Chianese, Ugo; Nicoletti, Maria Maddalena; Benedetti, Rosaria; Altucci, Lucia (Frontiers in Genetics, 2020)
Epigenetics has achieved a profound impact in the biomedical field, providing new experimental opportunities and innovative therapeutic strategies to face a plethora of diseases. In the rare diseases scenario, Beckwith-Wiedemann syndrome (BWS) is a pediatric pathological condition characterized by a complex molecular basis, showing alterations in the expression of different growth-regulating genes. The molecular origin of BWS is associated with impairments in the genomic imprinting of two domains at the 11p15.5 chromosomal region. The first domain contains three different regions: insulin growth like factor gene (IGF2), H19, and abnormally methylated DMR1 region. The second domain consists of cell proliferation and regulating-genes such as CDKN1C gene encoding for cyclin kinase inhibitor its role is to block cell proliferation. Although most cases are sporadic, about 5-10 % of BWS patients have inheritance characteristics. In the 11p15.5 region, some of the patients have maternal chromosomal rearrangements while others have Uniparental Paternal Disomy UPD(11)pat. Defects in DNA methylation cause alteration of genes and the genomic structure equilibrium leading uncontrolled cell proliferation, which is a typical tumorigenesis event. Indeed, in BWS patients an increased childhood tumor predisposition is observed. Here, we summarize the latest knowledge on BWS and focus on the impact of epigenetic alterations to an increased cancer risk development and to metabolic disorders. Moreover, we highlight the correlation between assisted reproductive technologies and this rare disease. We also discuss intriguing aspects of BWS in twinning. Epigenetic therapies in clinical trials have already demonstrated effectiveness in oncological and non-oncological diseases. In this review, we propose a potential “epigenetic-based” approaches may unveil new therapeutic options for BWS patients. Although the complexity of the syndrome is high, patients can be able to lead a normal life but tumor predispositions might impair life expectancy. In this sense epigenetic therapies should have a supporting role in order to guarantee a good prognosis.